Performance Improvement of Multi Level Inverter fed Vector Controlled Induction Motor Drive for Low Speed Operations - K. Satyanarayana; B. Anjaneyulu; K. Siva Prasad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this paper, the analysis of space vector based multi level inverter (MLI) fed vector controlled induction motor drive for low speed oparations is presented. The performance of indirect field oriented controlled induction motor drive (IMD) is poor with two-level inverter for low speed operations (LSO). The reduction in performance and peak value of torque are mainly due to the non-linearity caused by stator voltage drop and inverter. Hence the performance factors of induction motor drive are analysed with the multi level inverters under different operating conditions. In this approach, the steady state ripple content in the current and torque waveforms are reduced and that to ripple content of torque is reduced from 0.15 to 0.05 under steady state with five-level inverter. When there is a step change in the load torque, the momentary decrease in speed with five-level inverter is less when compared two and three-level inverters and the speed response reaches the reference value very quickly with five-level inverter during steady state and transient periods. So the overall performance of drive is improved with five-level inverter when compared to two-level and three- level inverters under low speed operations.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.4968